Integrated Monetary and Financial Policies for Small Open Economies - Basu, Suman S.; Boz, Emine; Gopinath, Gita; Roch, Francisco; Unsal, D. Filiz (Econometrica, 2025)
We develop a tractable small‐open‐economy framework to characterize the constrained efficient use of the monetary policy rate, foreign exchange (FX) intervention, capital controls, and domestic macroprudential measures. The model features dominant currency pricing, positive premia on local currency debt arising from financiers' portfolio constraints, and occasionally‐binding external and domestic borrowing constraints. We characterize the conditions under which the traditional prescription—relying solely on the policy rate and exchange rate flexibility—remains sufficient, even in the presence of externalities. By contrast, to manage noise trader flows into and out of the local currency debt market, FX intervention and in some cases capital inflow taxes should be used instead of the traditional prescription. Moreover, if a country faces a mix of local currency premia and external borrowing constraints, we establish that certain regulations to limit FX mismatch may alleviate the external borrowing constraint but exacerbate the local currency premia. Finally, we show that capital controls may dominate domestic macroprudential measures in cases when external shocks trigger stress in domestic housing markets.